Do Tax Policies in Nigeria Have Similar Implications for the Manufacturing Sector Output? - Musa Abdullahi Sakanko; Jeremiah Nshe Manomi; Abubakar Ijoko; Usman Abdulkareem Audu (Faculty of Economic and Business, 2022)
The study examines whether tax policies in Nigeria have similarimplications on the manufacturing sector’s output during the1994Q1-2020Q4 period using the ARDL bounds testing approach.The bounds testing result suggests the presence of cointegrationbetween tax policies and the manufacturing sector output. Further,the estimation results demonstrate that company income tax (CIT)and import tax are positively related to manufacturing sectoroutput. In contrast, value-added tax (VAT) has a negative effecton the manufacturing sector output, both in the short- and longterm.In addition, the results of the Granger causality test indicatea unidirectional causal relationship running from tax policies tothe manufacturing sector output and not vice versa. Thus, policiesand measures are recommended to prioritize the CIT and importtax, review the assortment in the VAT, and ensure accountabilityand transparency in the tax system.JEL Classification: C32, L60, H22